THE POSITIONING AND RESHAPING OF AESTHETIC EDUCATION IN DANCE EDUCATION AT ART COLLEGES AND UNIVERSITIES UNDER THEINHERITANCE OF THE CHINESE CULTURE - Ni, Ding (E-Journal VFU, 2024)
In the new era President Xi Jinping has made a comprehensive and in-depth exposition on a series of major theoretical and practical issues on the inheritance and development of the Chinese culture. In the speech at the symposium on literary and artistic work, President Xi pointed out that there has always been a consistent spiritual pursuit, characteristics and context. То explain the positioning and reshaping of aesthetic education in talent cultivation of dance education at art colleges and universities from the perspective of the Chinese cultural inheritance what should be examined is the relationship between culture and aesthetic education, technologies and art under the connotation of cultural spirits, the current implementation of aesthetic education from the perspective of dance educating abilities, and further it should be investigated the path for the positioning and reshaping of dance education in art colleges and universities under the framework of cultural confidence.